Improving Photoluminescence Quantum Yield of CdTe Quantum Dots Using a Binary Solvent (Water + Glycerin) in the One-Pot Approach Synthesis - Rosa,Lucas T. A. da (2021)
The present work describes the comparison of the optical and structural properties between CdTe quantum dots (QD) synthesized in water and in the binary solvent (water + glycerin) via one-pot approach synthesis. The optical properties of the nanocrystals obtained with different synthesis parameters were characterized by UV-visible and photoluminescence spectroscopies. The structural chracterization were performed by Fourier transform infrared spectroscopy (FTIR), zeta potential, size-distribution by dynamic light scattering (DLS), X-ray diffraction (XRD), and also by high-resolution transmission electron microscopy (HRTEM). The optical properties of CdTe QD when synthesized in the binary solvent were better, resulting in the increase of photoluminescence quantum yield (Φƒ). The CdTe QD prepared in 120 min, at pH 10.0, in the Cd:Te molar ratio 20:1, using the molar ratio 1:1.5 of Cd:TGA (thioglycolic acid), exhibited a narrow photoluminescence band and enhanced Φƒ for the samples synthesized in a binary solvent in comparison to water solvent (58.4 and 49.5%, respectively).